2005
DOI: 10.1080/08880010590896288
|View full text |Cite
|
Sign up to set email alerts
|

Non-Hodgkin Lymphoma Presenting With Uveitis Occurring After Blunt Trauma

Abstract: We report here an unusual patient suffering from visual loss with refractory uveitis which was occured after a blunt trauma to her left eye. While in the hospital cervical lymph node and anterior chamber aspiration cytology with immunohistochemical staining were performed. The histopathologic diagnosis was highly malignant B-cell non-Hodgkin lymphoma. After the inflammation of the eye was regressed with chemotherapy, pars plana vitrectomy-lensectomy was performed. She was free of inflammation and the best corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Non‐Hodgkin's lymphoma can have multiple etiologies, including immunodeficiency, viral infections (such the Epstein Barr virus), radioactive contaminations, and hybrid genes resulting from translocation 3 . There have been several reports in which lymphoma developed after blunt trauma, the majority were described in the head and neck; 3–5 in the chest wall, the literature presents cases of lymphoma in patients with a long history of chronic tuberculous pyothorax or a history of artificial pneumothorax, and most cases are reported in Japan 6 . These lymphoma have been designated pyothorax‐associated lymphoma and show features of DLBCL similar to those developed from other chronic inflammatory conditions, 7 such as the use of metallic implants in bones and joints, 8 chronic osteomyelitis, 9 chronic venous ulcer 9 and the use of surgical mesh implant 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Non‐Hodgkin's lymphoma can have multiple etiologies, including immunodeficiency, viral infections (such the Epstein Barr virus), radioactive contaminations, and hybrid genes resulting from translocation 3 . There have been several reports in which lymphoma developed after blunt trauma, the majority were described in the head and neck; 3–5 in the chest wall, the literature presents cases of lymphoma in patients with a long history of chronic tuberculous pyothorax or a history of artificial pneumothorax, and most cases are reported in Japan 6 . These lymphoma have been designated pyothorax‐associated lymphoma and show features of DLBCL similar to those developed from other chronic inflammatory conditions, 7 such as the use of metallic implants in bones and joints, 8 chronic osteomyelitis, 9 chronic venous ulcer 9 and the use of surgical mesh implant 10 .…”
Section: Discussionmentioning
confidence: 99%
“…During our research, reported cases related to lymphoma usually, initiate at head after blunt trauma, such as scalp, [ 1 ] oculus, [ 2 ] and uveitis. [ 4 ] Blunt trauma can cause local tissue degeneration, and necrosis, and finally, result in cell atypia during the healing process. [ 2 ] Almost all of the reported cases were non- Hodgkin's lymphoma, but there was not any case of post-trauma nonleukemic GS.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] But for hematological diseases like non-Hodgkin's lymphoma, the development of tumor usually happened within a year. [ 1 4 ] If there would be more attention on the association between trauma, and tumorgenesis, early follow-up of the change in the lesion could be achieved. Meanwhile, lack of recognition of this possibility may result in delay of diagnosis and timely treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] PUBMED search revealed about seven cases of malignant lymphoma reported after a history of previous trauma, among those five were reported in head and neck region. [26789] These lymphomas manifested 1–2 months after blunt trauma to the occipital region, cheek, forehead, periorbital and eye.…”
Section: Introductionmentioning
confidence: 99%